2020
DOI: 10.1177/1476750320910491
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing STEM equity programs with action research

Abstract: Cultural diversity in professional fields, including science, technology, engineering, and math (STEM), leads to greater innovation due to the improved range of ideas,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In their study on enhancing STEM equity programs with action research Barber et al (2020) provide guidelines that include recommendations to explore processes rather than outcomes and to use an action research framework at the project onset. Findings showed the most informative data was collected through interviews and informal interactions with participants, which was then utilised to identify and justify changes to the curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study on enhancing STEM equity programs with action research Barber et al (2020) provide guidelines that include recommendations to explore processes rather than outcomes and to use an action research framework at the project onset. Findings showed the most informative data was collected through interviews and informal interactions with participants, which was then utilised to identify and justify changes to the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The action research method has been shown to promote independent, autonomous learning in educational settings (Gibbs et al, 2017) and has provided successful outcomes for STEM students (Schiller et al 2018;Burrows and Borowczak, 2019;Barber et al, 2020). In this study the curriculum is developed through repeated action research spirals that contain the teaching activities and feed forward the findings from the delivery to refine the next version in an evolutionary cycle.…”
Section: Action Research As Methods and Methodologymentioning
confidence: 99%